Experimental Evidence on the Impacts of Need‐Based Financial Aid: Longitudinal Assessment of the Wisconsin Scholars Grant. (30th December 2019) - Anderson, Drew M.; Broton, Katharine M.; Goldrick‐Rab, Sara; Kelchen, Robert
Abstract: We conduct the first long‐term experimental evaluation of a need‐based financial aid program, the privately funded Wisconsin Scholars Grant. Over multiple cohorts, the program failed to increase degree completion and graduate school enrollment up to 10 years after matriculation. The program did reduce time‐to‐degree for some students and modestly increased the number of STEM degrees earned. The lack of robust effects raises important questions about the conditions necessary for financial aid to benefit students.